Longitudinal Change of Forearm-Hand Inertia Value and Shoulder Musculature Using Dual X-ray Absorptiometry in Youth Japanese Baseball Players: Implications for Elbow Injury - Toshiharu Tsutsui; Toshihiro Maemichi; Satoshi Iizuka; Suguru Torii (MDPI AG, 2020)
It is important to understand the timing of the maximum increase of forearm-hand inertia value and lean body mass (LBM) of the shoulder girdle musculature when elbow injury frequently occurs. This study aimed to clarify the discrepancies of those in youth baseball players. Forty-three male baseball players (8- to 14-years-old) participated in this study. The forearm-hand inertia value and LBM of the shoulder girdle musculature were calculated using dual-energy X-ray absorptiometry (DXA). A cubic spline fit was applied to the annual increase forearm-hand inertia value and LBM of the shoulder girdle musculature for each chronological age and years from peak height velocity (PHV) age. As a result of cubic splines fitting, the peak timing for forearm-hand inertia value and LBM of the shoulder girdle musculature was 12.42 and 12.75 years in chronological age, −0.66 and −0.11 years in PHV age. Therefore, the peak timing of forearm-hand inertia value was about 4 months earlier in chronological age and half a year earlier in PHV age than LBM of the shoulder girdle musculature. Acquiring sufficient shoulder girdle musculature during the period when the growth of the shoulder girdle musculature cannot catch up with forearm-hand inertial value is necessary to reduce the elbow load while throwing.